Effects of feeding rate and formula fineness degree of ring die pellet mill on mechanical property, physical quality, energy requirements, and production cost of poultry diets - Metwally, Khaled A.; Zaki, Reda I.; Fouda, Sally S.; Alruhaimi, Reem S.; Alqhtani, Haifa A.; Aldawood, Nouf; Mahmoud, Ayman M.; Naiel, Mohammed A. E. (International Journal of Agricultural and Biological Engineering, 2023)
The effect of a machine feeding rate (FR; 1, 1.5 and 2 Mg/h) and/or three levels of selected fineness degree (FD; 3, 5 and 7 mm) on machine performance, pellet physical parameters, required energy and production cost of three main types of broilers diets were examined in this experiment. The examined broiler diets were formulated to meet the Ross 308 strain requirements. A complete factorial design (3×3×3) was used to identify the effects of studied factors on the pellet mill machine and pellet production. The obtained results indicated that the pellet mill productivity significantly (p˂0.001) improved through increased pellet mill feeding rate level. In addition, the machine pelleting efficiency was found to be significantly affected by all studied variables and their interactions. While the total power consumption of the machine showed no variations under the impact of the tested factors or with any of their combinations. Regarding the pellet physical quality indices, all broiler diets with all selected FD and lower FR had the maximum durability and bulk density levels. Furthermore, lower feeding rates were associated with higher hardness degrees. The lowest production costs were substantially correlated with high FR and intermediate FD (5 mm). Furthermore, production costs were determined to be reduced in finisher broiler diets under different feeding rates. Moreover, manufacturing costs of finisher broiler meals were observed to decrease in several feeding rates. Overall, these findings indicate the capabilities of producing high-quality pellets and reducing the needed production costs by optimizing feeding rates to 2 Mg/h and 2 mm fineness in broiler diets. Keywords: feeding rate, fineness degree, broiler diets, pellet quality, production cost DOI: 10.25165/j.ijabe.20231603.7564 Citation: Metwally K A, Zaki R I, Fouda S S, Alruhaimi R S, Alqhtani H A, Aldawood N, et al. Effects of machine feeding rate and formula fineness degree of ring die pellet mill on mechanical property, physical quality, energy requirements, and production cost of poultry diets. Int J Agric & Biol Eng, 2023; 16(3): 30–36.